Effects of Household Washing on the Reduction of Microbiological Contamination of Minimally Processed Vegetables - A. Kukułowicz (Scientific Journal of Gdynia Maritime University, 2018)
Fresh vegetables are highly recommended in any diet, virtually without quantitative restriction. The consumption of minimally processed vegetables has increased in recent years, among others due to their convenience and health benefits. However, these products are also a great base for the growth of pathogenic micro-organisms. The aim of this study was to assess the impact of the household washing of minimally processed salads on the reduction of their microbial contamination. Used in this study double 30-second washing of salads under running water has resulted in reduction of the number of Staphylococcus aureus by about 1 logarithmic cycle, whereas Escherichia coli were not found in those products.